Essays on health care operations management - Catena, R (2015)
The aim of operations management in health care is to enhance the provision of services to patients and to decrease costs. Overall worldwide health care expenditures represent around 10.5% of the global GDP and are projected to increase at an annual rate of 5.3% from 2015 to 2017 [74]. In order to investigate how to curb health care costs, I study the English NHS, a health care system that provided universal care to around 54 million people in 2014 [243]. The NHS has launched many initiatives to improve the performance of hospital operations such as the "QIPP" program, which has the objective to save £20 billion of costs by 2015 [98]. Given this framework, this research aims to contribute to the theory that is guiding these operational changes, using data on all admissions to hospitals and focussing on the inguinal hernia, one of the most common surgical procedures [86]. In the next chapters, this research describes inguinal hernia care delivery in the English NHS, examines the impact of spillovers and complementarities on costs, and investigates the effects of length of stay reduction on risk of re-admission and risk of death. The findings of this thesis indicate that one of the possible problems in the delivery of inguinal hernia care in the NHS is the decrease in the number of elective operations performed and the increase in readmission rates. They also clarify how decisions on allocation of resources can affect hospital expenditures by showing that loss in focus can increase health care costs and by pointing out that there is little evidence to support the theory of spillovers and complementarities in the surgical context. Finally, the results of this research can be used to suggest the logic of a policy to decrease length of stay that can inform hospital decisions and can decrease hospital costs.